2003
DOI: 10.1002/elps.200390152
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic range of fluorescence detection and base‐calling accuracy in DNA sequencer based on single‐photon counting

Abstract: Recently, we developed a family of high-performance automated capillary DNA sequencing instruments based on a single-photon detection of fluorescently labeled DNA fragments. Our machines employ digital and broadband techniques, essential for achieving superior instrument sensitivity and dynamic range. In the present paper, we discuss limitations of the instrument's performance caused by the nonlinearity of single-photon detectors as well as methods for nonlinearity compensation which increase the detection dyn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 26 publications
(12 reference statements)
0
11
0
Order By: Relevance
“…1), have provided motivation for the development of improved single-photon sources 28 and single-photon detectors. In addition to quantum-information science, singlephoton detectors are used for a wide range of applications, including bioluminescence detection, 38 DNA sequencing, [39][40][41][42] Förster resonance energy transfer (FRET) for studying protein folding, [43][44][45] light detection and ranging (LIDAR) for remote sensing, 46,47 and light ranging on shorter scales, 48 optical time domain reflectometry, [49][50][51][52][53][54][55] picosecond imaging circuit analysis, [56][57][58][59][60][61] single-molecule spectroscopy [62][63][64][65][66][67][68] and fluorescence-lifetime measurements, 69 medical applications such as diffuse optical tomography 70 and positron emission tomography, 71 and finally applications such as traditional and quantum-enabled metrology. [72][73][74][75][76][77][78][79][80]…”
Section: B Why Produce and Detect Single Photons?mentioning
confidence: 99%
“…1), have provided motivation for the development of improved single-photon sources 28 and single-photon detectors. In addition to quantum-information science, singlephoton detectors are used for a wide range of applications, including bioluminescence detection, 38 DNA sequencing, [39][40][41][42] Förster resonance energy transfer (FRET) for studying protein folding, [43][44][45] light detection and ranging (LIDAR) for remote sensing, 46,47 and light ranging on shorter scales, 48 optical time domain reflectometry, [49][50][51][52][53][54][55] picosecond imaging circuit analysis, [56][57][58][59][60][61] single-molecule spectroscopy [62][63][64][65][66][67][68] and fluorescence-lifetime measurements, 69 medical applications such as diffuse optical tomography 70 and positron emission tomography, 71 and finally applications such as traditional and quantum-enabled metrology. [72][73][74][75][76][77][78][79][80]…”
Section: B Why Produce and Detect Single Photons?mentioning
confidence: 99%
“…Linearity of optical cross-talk is obvious as long as the measured photocount rate stays within the linear range of the PMT [29]. ( )…”
Section: Cross-talk Removal Methodsmentioning
confidence: 99%
“…The methods for characterization and compensation of non-linearity of a single photon detector are described in detail in [29]. If the number of lanes M in the system is equal to the number of photodetection channels, then C is a square ( ) N N × matrix, and the Eq.…”
Section: Optical Cross-talkmentioning
confidence: 99%
“…The shortest pulse duration resolved by the counter was less than 2 ns, and a minimum pulse amplitude ∼1.5 V. Our tests of the linearity of the developed single photon detector showed an extremely broad range of linear photon counting (up to 2 × 10 7 photocounts/s) which exceeds detection dynamic range of any commercial single photon detectors. Implementation of the non-linearity correction procedure (Gavrilov et al, 2003) allows for additional expansion of the linear range. Comparison of the photon detection efficiency (PDE) of the developed detector and the most efficient commercially available single photon detector SPCM-AQR-12-FC (Perkin-Elmer, Canada) showed that at 490 nm the PDE of the 32-channel PMT detector constituted ∼20% of the PDE of the SPCM and it decreased down to 5% at 610 nm.…”
Section: Processing Of Dna Sequencing Datamentioning
confidence: 99%
“…During last several years our research group has developed a number of single photon sensors with increased dynamic range and has demonstrated first DNA sequencing instruments possessing an ultra high sensitivity and a large detection dynamic range (Alaverdian et al, 2002;Gavrilov et al, 2003Gavrilov et al, , 2006Dhulla et al, 2005Dhulla et al, , 2007.…”
Section: Introductionmentioning
confidence: 99%